Virtual Empathy: A Systematic Review of the Impact of Digital Communication on Interpersonal Relationships and Social Dynamics - Čekić, Elvira (International Journal of Psychology, 2025)
Purpose: The aim of this systematic review is to determine how virtual empathy, as a multidimensional psychological construct, manifests within digitally mediated interactions and to examine its impact on emotional regulation, interpersonal relationships, and patterns of social connectedness. The analysis encompasses both cognitive and affective components of empathy, their variations depending on communication modalities, as well as empathy-related dysfunctions conditioned by technological factors. The review also includes studies that investigate the role of Artificial Intelligence (AI) and Virtual Reality (VR) in the modulation of emotional processes, moral evaluation, and neurocognitive sensitivity within digital contexts. Methodology: This systematic review includes the analysis of 42 empirical studies published between 2013 and 2024, identified through a structured search of major scientific databases, including Scopus, Web of Science, PsycINFO, and Google Scholar. A qualitative content analysis was used to synthesize key findings, with a focus on psychological and neurocognitive mechanisms relevant to the phenomenon of virtual empathy. The selected studies span various research designs, experimental, longitudinal, survey-based, and meta-analytic, and examine digital mechanisms such as emojis, avatars, algorithmic content personalization, and interactive AI-based systems. The analytical approach is oriented toward identifying how digital environments compensate for the absence of nonverbal cues and mediate empathic processes through symbolic and immersive technologies. Findings: The systematic review suggests that virtual empathy has a significant impact on emotional regulation and the quality of interpersonal relationships in digital contexts. Digital platforms, especially those utilizing Virtual Reality (VR), can facilitate the development of cognitive and affective empathy, particularly when the content stimulates perspective-taking and emotional resonance. However, specific limitations of digital communication, including the absence of nonverbal cues, emotional superficiality, and the dominance of algorithmically shaped “echo chambers,” may substantially reduce the authenticity of empathic responses. Furthermore, chronic exposure to digitally mediated content may lead to gradual desensitization to others’ emotions, potentially impairing moral sensitivity and eroding social cohesion. Unique Contribution to Theory, Practice, and Policy: This review advances theoretical understanding through the synthesis of classical frameworks, such as Social Presence Theory and Media Richness Theory, with emerging constructs like simulated affectivity and algorithmic mediation, offering an enhanced model of digital empathy. It provides insights into how virtual environments shape moral reasoning, emotional regulation, and prosocial behavior. It provides insights into how virtual environments shape moral reasoning, emotional regulation, and prosocial behavior. At the practical level, it offers recommendations for the design of emotionally intelligent digital tools and educational programs aimed at preventing empathic desensitization. At the policy level, it highlights the need for ethical standards to regulate algorithmic content and promote inclusive, emotionally authentic communication. It also opens avenues for interdisciplinary research into the psychological implications of contemporary technologies.